PHOTOSYNTHETIC PIGMENT COMPOSITION OF ICE ALGAL AND PHYTOPLANKTON ASSEMBLAGES IN EARLY SPRING IN SAROMA KO LAGOON, HOKKAIDO, JAPAN (19th Symposium on Polar Biology) - カシノ, ヤスヒロ; フジモト, クミコ; アカマツ, アケミ; コイケ, ヒロユキ; サトウ, カズヒコ; クドウ, サカエ; KASHINO, Yasuhiro; FUJIMOTO, Kumiko; AKAMATSU, Akemi; KOIKE, Hiroyuki; SATOH, Kazuhiko; KUDOH, Sakae (National Institute of Polar Research, 1998)
P(論文) Ice algae were collected from sea ice of 35 cm thickness at Saroma Ko lagoon in early February, 1996 The sea ice was sectioned into 5cm height intervals from the bottom so as to separate ice algae according to vertical distribution. Phytoplankton were also harvested at the same site in mid-April, 1996, a few days after the sea ice disappeared. Photosynthetic pigments of ice algae and phytoplanktonic algae were analyzed by reverse-phase HPLC (high performance liquid chromatography). Chlorophyll a, c, β-carotene, and several kind of carotenoids, such as fucoxanthm, diadmoxanthin or diatoxanthin, were detected, but chlorophyll b was not recognized, suggesting that diatom species were predominant in ice algae and phytoplanktonic algae. The pigment composition of ice algae changed according to their vertical distribution The ratios of chlorophyll c and carotenoids to chlorophyll a in ice algae harvested from the top of the sea ice were higher than those of ice algae collected from the lower position, in other words, ice algae in the lower position, i e., where they experienced less light decreased the ratio This suggests that ice algae adopted very peculiar light-shade adaptation, because vascular plant or green algae have the opposite response so that they decrease the ratio of auxiliary pigments to chlorophyll a with increasing light intensity Pigment composition of phytoplanktonic algae resembled that of ice algae collected from the uppermost portion of sea ice. departmental bulletin paper